Target selection method on the occluded and distant object in handheld augmented reality - Ajune Wanis Ismail; Nur Ameerah Abdul Halim; Rohaya Talib; Ahmad Johari Sihes (Institute of Advanced Engineering and Science, 2023)
Existing interaction techniques within handheld augmented reality (AR) have frequently used touchscreen input (pure two-dimensional (2D) pointing and clicking) from the handheld device's display for target selection on the virtual object. However, performing accurate target selection on a distant target object becomes challenging as the target object will appear smaller when the distance increases. Aside from that, the difficulty increases in performing target selection when another virtual object obscures the distant virtual object. Therefore, this study aims to present a target selection method to perform the target selection. We enable the raycasting technique with real hand gesture for the target selection method on the occluded and distant object in handheld AR. The leap motion device is mounted at the back of the handheld device to track the real hand gesture. The markerless tracking technology of simultaneous localization and mapping (SLAM) is implemented to enable the AR environment. Based on the results, the aim of this study was achieved.